2021
DOI: 10.1080/00313831.2021.1939144
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability as an Emotional Dimension in Student Teachers’ Narrative Identities Told With Self-Portraits

Abstract: This article focuses on what student teachers tell about the emotional dimension of their identities with self-portraits. Narrative interviews with self-portraits were conducted with two student teachers in the final stages of their studies. The interviews were analysed by using narrative analysis, followed by a thematic cross-analysis of the two emplotted stories. The findings emphasise the importance of vulnerability as a significant emotional dimension of student teachers' identities, showing them to be vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…As to their imagination, it was found that contextual discourses and particularities played a key role in the excessive emotional vulnerability of the student teachers to the extent that they doubted their identity as future teachers. Holappa et al (2022) and Song (2016) have extensively discussed how structural forces and contextual peculiarities are likely to impose negative emotions on teachers and the subsequent vulnerability that they go through. Our findings add to this discussion by showing how emotional vulnerability not only influences teachers' present conceptions but also negatively influences their prospective perceptions and identities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to their imagination, it was found that contextual discourses and particularities played a key role in the excessive emotional vulnerability of the student teachers to the extent that they doubted their identity as future teachers. Holappa et al (2022) and Song (2016) have extensively discussed how structural forces and contextual peculiarities are likely to impose negative emotions on teachers and the subsequent vulnerability that they go through. Our findings add to this discussion by showing how emotional vulnerability not only influences teachers' present conceptions but also negatively influences their prospective perceptions and identities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings underlined that power relations and public expectations made teaching gradually insecure for Chinese teachers. Likewise, Holappa et al (2022), by adopting a narrative approach, probed the emotions of two student teachers' professional identities through self-portraits.…”
Section: Language Teacher Emotional Vulnerabilitymentioning
confidence: 99%
“…Inspired by scholars who have recently explored drawing, collage, self-portrait, and other visual art forms as research tools (e.g., McKay and Barton, 2018;Culshaw, 2019;Holappa et al, 2021), this study asked: Knowing that professional identity work is part of the hidden curriculum of a teacher candidate's student teaching experience (Britzman, 2003), how might an arts-based reflection help candidates to express their thoughts, feelings, and actions regarding this often invisible process of learning to teach? In keeping with Holappa et al's (2021) work into student teacher vulnerability, our teacher candidates, especially candidates who had a challenging student teaching experience, benefited from the opportunity to express these challenges in a low risk environment through anonymized artwork. As one candidate shared in a written reflection about the activity: At first, I thought it seemed like humdrum busywork that I did not really want to do.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, teacher education researchers have demonstrated that visual art forms-collage, self-portraits, drawings, etc.-are particularly powerful and creative approaches to promoting self-reflection and continued teacher identity development 10.3389/feduc.2022.970406 in relationship to these complex dynamics (e.g., Beltman et al, 2015;Culshaw, 2019;McKay, 2019McKay, , 2021Holappa et al, 2021). McKay and Barton (2018) write, "using arts-based approaches can enhance the quality and depth of reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, Teacher emotions not only affect teachers themselves but also have an impact on their students ( Chen, 2021 ). And some researchers have begun to pay attention to the emotional problems of pre-service teachers ( Uitto et al, 2015 ; Timoštšuk et al, 2016 ; Zhu, 2017 ; Holappa et al, 2021 ). Pre-service teachers have the dual identities of students and future teachers, and the cultivation of their teaching practice ability has always been an important topic and key link in normal universities ( Chen et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%